KARAKTERISTIK FLAKES YANG DIHASILKAN DARI TEPUNG HANJELI (Coix lacryma jobi L.) TERMODIFIKASI DENGAN METODE HEAT MOISTURE TREATMENT - Hervelly Hervelly (Department of Food Technology, Universitas Pasundan, Bandung, 2020)
The aim of this study was obtained suitable conditions on the modification of hanjeli flour with variations of hanjeli flour moisture and heating temperature so as to improve the characteristics of hanjeli flour and increased its used into flakes products. The benefit of this study was an increase the added value of local raw materials that widely used, to utilized the technology of modification method of Heat Moisture Treatment for food processing made from raw hanjeli for hanjeli characteristics can be applied to flakes products. The study was divided into three stages: preliminary, main and second research. The experimental design used in this study was Randomized Block Design (RBD) consist of two factors: moisture level and heating temperature with 3 levels and 3 time replications, so that 27 experimental units were obtained. The treatment design consisted of variations was conducted in moisture a1 (20%), a2 (25%), a3 (30%), and heating temperature b1 (90oC), b2 (100oC), b3 (110oC). The result of this st dy was obtained that the selected sample were a3b1 (moisture level 30% and heating temperature 90oC) with an average water content 9,657%, amylose 8,393% and setback viscosity 955,000 cP. The preparation of flakes from selected modified hanjeli flour was tested for water content, amylose, water absorption of flakes and the organoleptic response.